Bullying Perpetration and Perceived Parental Monitoring: A Random Intercepts Cross-Lagged Panel Model. Issue 8 (November 2021) - Doty, Jennifer L.; Lynne, Sarah D.; Metz, Allison S.; Yourell, Jacqlyn L.; Espelage, Dorothy L.
Although parental monitoring often reduces youth risk behaviors, some research on bullying perpetration has found that parental monitoring deters bullying while other research has found a null effect or a positive effect. We investigated the bidirectional relationships of bullying perpetration and parental monitoring from age 11 to 18 years, leveraging data from four middle and six high schools in the Midwest ( N = 3, 549 students). We observed within-student stability in bullying perpetration and parental monitoring across time. Bullying perpetration had a prospective, negative association with parental monitoring from ages 11 to 12. However, parental monitoring predicted lower levels of bullying perpetration from ages 13 to 14. In early adolescence, youth who bully may be emboldened by a lack of perceived parental monitoring. Parental monitoring through establishment of house rules and awareness of risk during early to middle adolescence may deter bullying perpetration.